PRESENTATION Nº37 Eng - Editor, El (Última Década, 2020)
The current issue begins with the section "Contemporary Youth Conditions," comprising three contributions related to the notions of youth trajectories and transitions. The first article, "Juvenile migration from paraguay to Argentina: Living conditions and duration of networks" by ANA MIRANDA, MARÍA CRISTINA CRAVINO, and SANTIAGO MARTÍ, presents the results of a binational research project on youth migration. Also focusing on the Argentinean reality, ANALÍA ELIZABETH OTERO, i n her paper titled "Debates and Paradoxes in Educational and Occupational Trajectories: An Analysis of Perspectives, Actions, and Limitations Among Argentinean Youth," identifies recurring elements and differentiating factors in the life paths of young ind ividuals in educational, work, and family contexts. ÓSCAR DÁVILA and FELIPE GHIARDO, from the Chilean context, contribute with "Transitions into adulthood: Generations and social changes in Chile" making an effort to explore the processes of becoming adult subjects, highlighting the ages, steps, and milestones that shape this journey.